Nurse-Led Multidisciplinary Heart Failure Group Clinic Appointments: Methods, Materials, and Outcomes Used in the Clinical Trial. (July 2015) - Smith, Carol E.; Piamjariyakul, Ubolrat; Dalton, Kathleen M.; Russell, Christy; Wick, Jo; Ellerbeck, Edward F.
Abstract : Background: The Self-management and Care of Heart Failure through Group Clinics Trial evaluated the effects of multidisciplinary group clinic appointments on self-care skills and rehospitalizations in high-risk heart failure (HF) patients. Objective: The purpose of this article is to (1) describe key Self-management and Care of Heart Failure through Group Clinics Trial group clinic interactive learning strategies, (2) describe resources and materials used in the group clinic appointment, and (3) present results supporting this patient-centered group intervention. Methods: This clinical trial included 198 HF patients (randomized to either group clinical appointments or to standard care). Data were collected from 72 group clinic appointments via patients' (1) group clinic session evaluations, (2) HF self-care behaviors skills, (3) HF-related discouragement and quality of life scores, and (4) HF-related reshopitalizations during the 12-month follow-up. Also, the costs of delivery of the group clinical appointments were tabulated. Results: Overall, patients rated group appointments as 4.8 of 5 on the "helpfulness" in managing HF score. The statistical model showed a 33% decrease in the rate of rehospitalizations (incidence rate ratio, 0.67) associated with the intervention over the 12-month follow-up period when compared with control patients ( χ 2 1 = 3.9, P = .04). The total cost for implementing 5 group appointments was 243.58 per patient. Conclusion: The intervention was associated with improvements in HF self-care knowledge and home care behavior skills and managing their for HF care. In turn, better self-care was associated with reductions in HF-related hospitalizations.